PENGARUH PELAKSANAAN MARKETING MIX TERHADAP KEPUASAN PELANGGAN INDUSTRI JASA KESEHATAN (KASUS RUMAH SAKIT SARI MUTIARA MEDAN ) - Krissanthi Atalia; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The issue of this research is the decline in the number of patient and outpatient Sari Mutiara Hospital Medan. In the last 3 years this indicates the occurrence decrease in patient satisfaction so that patients switched to other hospitals. The purpose of this study isto investigate the implementation of the marketing mix and determine patient satisfaction in Sari Mutiara Hospital Medan. The collection of data through questionnaires to 100 patients Sari Mutiara Hospital Medan. Results of a study of the marketing mix implemented Sari Mutiara Hospital Medan considered to be quite good. So also with the satisfaction of patients considered to be high satisfaction. Results calculated with SPSS. Showed that the marketing mix (X) positive effect on patient satisfaction / customer (Y) Hospital Sari Mutiara Medan.Key words : marketing mix, consumer satisfaction, sari mutiara hospital Medan